Survival outcomes of surgery and adjuvant chemotherapy in early-stage small cell and large cell lung cancer: a novel focus on tumors less than 1 cm - Jorge Raul Vazquez-Urrutia; Junjia Zhu; Shinkichi Takamori; Max Greenberg; Priyanka Bhatia; Takefumi Komiya (Discover Oncology)
Abstract Background The role of adjuvant chemotherapy in early-stage small cell lung cancer (SCLC) and large cell neuroendocrine carcinoma (LCNEC) remains unclear, particularly for small tumors. This study assesses the survival benefits of adjuvant chemotherapy after surgical resection with a novel focus on tumors less than 1 cm. Materials and methods Data from the National Cancer Database (NCDB) was extracted for patients with SCLC (n = 11,962) and LCNEC (n = 6821) who underwent surgical resection between 2004 and 2020. Exclusion criteria were limited survival (< 30 days), positive lymph nodes, distant metastases, large tumors (> 5 cm), residual microscopic disease, and neoadjuvant therapy. The primary outcome was overall survival (OS) from diagnosis, which was evaluated using Kaplan–Meier methods and multivariate Cox regression analyses. A propensity score matching (PSM) analysis was performed to compare outcomes in patients with SCLC and tumors ≤ 1 cm who received adjuvant chemotherapy versus surgery alone. Results The study involved 4114 SCLC and 3954 LCNEC patients. Adjuvant chemotherapy was associated with a significant increase median OS in both SCLC (6.26 vs. 4.18 years; p < 0.001) and LCNEC (7.02 years vs. 4.89 years; p < 0.001), while also being an independent predictor of better OS in SCLC (HR: 0.74) and LCNEC (HR: 0.75) (p < 0.001). The benefit was more noticeable in tumors ≤ 1 cm, showing a significant OS increase after PSM (median OS 7.34 vs. 5.02 years; p = 0.0048). Conclusion Adjuvant chemotherapy after surgery is associated with improved overall survival in stage I SCLC and LCNEC, particularly in SCLC tumors of 1 cm or less.